Staged Mucosal Advancement Flap versus Staged Fibrin Sealant in the Treatment of Complex Perianal Fistulas - S. J. van der Hagen; C. G. Baeten; P. B. Soeters; W. G. van Gemert (Gastroenterology Research and Practice)
Background. In this prospective randomised study, the staged mucosal advancement flap is compared with staged fibrin sealant application in the treatment of perianal fistulas. Methods. All patients with high complex cryptoglandular fistulas were randomised to closure of the internal opening by a mucosal advancement flap (MF) or injection with fibrin sealant (FS) after treatment with setons. Recurrence rate and incontinence disorders were explored. Results. The MF group (5 females and 10 males) with a median age of 51 years and a median followup of 52 months. The FS group (4 females and 11 males) with a median age of 45 years and a median followup of 49 months. Three (20%) patients of the MF group had a recurrent fistula compared to 9 (60%) of the FS group (P=0.03). No new continence disorders developed. Conclusion. Staged FS injection has a much lower success rate compared to MF.